Review of the pig-adapted African swine fever viruses in and outside Africa - Penrith, M.-L.; Heerden, J. van; Heath, L.; Okoth, Edward A.; Bastos, A.D.S. (MDPI, 2022)
The region in eastern, central and southern Africa (ECSA) where African swine fever (ASF) originated in a sylvatic cycle is home to all the p72 genotypes of ASF virus identified so far. While 20 of the 24 genotypes have been isolated from outbreaks in domestic pigs in the region, only five of the genotypes (I, II, VIII, IX, X) have an extended field presence associated with domestic pigs. Of the genotypes that appear to be strongly adapted to domestic pigs, two have spread beyond the African continent and have been the focus of efforts to develop vaccines against ASF. Most of the experimental ASF vaccines described do not protect against a wider spectrum of viruses and may be less useful in the event of incursions of different strains or where multiple genotypes co-exist. The other three pig-adapted strains that are currently restricted to the ECSA region might spread, and priority should be given to understanding not only the genetic and antigenic characteristics of these viruses but also their history. We review historic and current knowledge of the distribution of these five virus genotypes, and note that as was the case for genotype II, some pig-associated viruses have the propensity for geographical range expansion. These features are valuable for prioritizing vaccine-development efforts to ensure a swift response to virus escape. However, whilst ASF vaccines are critical for high-production systems, global food security relies on parallel efforts to improve biosecurity and pig production in Africa and on continued ASFV surveillance and characterisation in the ECSA region.